Policy Analysis of China’s Principal Rank System for Primary and Secondary Schools : Policies, Challenges, and Future Directions - Wang, HuaDong; Ma, Chao; Pei, Lijiao (Pacific International Journal, 2023)
The Principal Rank System for primary and secondary schools has undergone a nearly 30-year pilot phase, representing a significant reform in the realm of education management in China. However, challenges persist in advancing this reform, and the overall progress has been sluggish. This paper conducts a literature-based examination of the policy background and the implementation of the Principal Rank System. During the promotion of this reform, the implementation of the Principal Rank System encounters multiple challenges, including passive responses from certain principals, inquiries into the determination of principal professional ranks, and the varied impacts of the salary incentive mechanism. This paper analyzes these issues and proposes solutions to address them. It is imperative to establish a unified and stringent principal admission system, develop a comprehensive principal evaluation framework, modernize the principal training mechanism, set forth a rational principal ranking system, enhance the principal duty station exchange system, address income disparities among regions, and augment feedback mechanisms following expert reviews to foster holistic educational development.